Analisis Perilaku Konsumsi Kopi oleh Generasi Z di Kota Surakarta - Rahmawati Setiyani; Lathifah Khairani; Rajendra Agidya Putra (LPPM Universitas Malikussaleh - Indonesia, 2026)
Consumption of coffee in Indonesia has increased alongside changes in people's lifestyles, particularly among the younger generation. Surakarta is a relatively advanced city, both economically and socially. Surakarta’s high urbanization rate and youthful demographic profile provide a fertile environment for the coffee retail sector. Consequently, this study examines the consumption behaviors of Generation Z in the region. Utilizing a descriptive quantitative method with a survey approach, this study sampled 30 samples. Research findings on coffee consumption behavior among Generation Z in Surakarta revealed that the majority of respondents had adopted a coffee-drinking routine for more than three years. This phenomenon indicates a deep integration between coffee consumption and contemporary behavioral patterns and lifestyles in this demographic group. Coffee is consumed moderately, at 2–3 times per week, with most people tending to order one cup each time. The most popular time to drink coffee is at night, suggesting that it plays a role in supporting study, work and social activities. Cappuccino is the most popular type of coffee drink, reflecting Generation Z's preference for coffee with a balanced taste and a milk base. The most popular places to purchase coffee are warung or angkringan, suggesting that affordability, accessibility and a relaxed atmosphere are the main considerations when purchasing coffee.